Computerized Acoustical Techniques For Respiratory Flow-Sound Analysis: A Systematic Review - Muthusamy, Priya Devi; Sundaraj, Kenneth; Abd Manap, Nurulfajar (Springer, 2019)
Computerized respiratory sound analysis has recently captured the attention of researchers, and its implementation can assist physicians in the diagnosis of pulmonary pathologies. The relationship between respiratory sounds and breathing flow reveals the pathophysiology of the respiratory system and can be used as a basis for acoustical airflow estimation. Respiratory sound signals are also acoustically analysed for the detection of breath phases. Although this research area is being actively studied, the available literature has not been reviewed. This manuscript highlights the previous studies that focused on the use of computer-based acoustical techniques for the analysis of respiratory sounds and airflow. Articles related to computerized respiratory flow-sound analysis were identified through a search of the Scopus academic database, and 66 articles were ultimately selected for this systematic review. A brief overview of the subject details, auscultation sites, respiratory manoeuvres, sound parameters of interest and techniques used is provided. The findings revealed the following: (1) deterministic relationships can be established between airflow and respiratory sounds, (2) an established strong flow-sound correlation can be used for airflow estimation, (3) breath phase detection and identification without flow measuring devices remains in the infancy research stage and (4) further research needed to examine the potential of computerized respiratory sound analysis in revealing the pathophysiology of airways for future clinical implementation. This review concludes by discussing the possibilities and recommendations for further advancements in computerized acoustical flow-sound analysis.